THE ROLE OF HEALTH CARE IN THE REGION AND THE OBJECTIVE NEED FOR ITS DEVELOPMENT (Marketing Journal, 2025)
This article examines the role of the healthcare sector in the region and the objective nature of its development. It also presents conclusions on the effective study of the role of the healthcare sector in the region and the objective nature of its develo pment.
Keywords: region; healthcare; sector; population; healthcare system; research